Prevalence of adverse birth outcomes and disparity of unmarried women in South Korea: a systematic review - Yeani Choi; Gyeongsil Lee; In Gyu Song; Ock Joo Kim; Sang Min Park (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background In this study, we aim to analyze the association between different types of cohabitation status and obstetric outcomes of preterm births (PTB), low birthweight (LBW), small for gestational age (SGA) and achieve a manifestation of social marginalization among varied marital status of women in South Korea. # Methods The study compared the birth outcomes of legally unmarried women with record of cohabitation (cohabited single), legally unmarried women with no record of cohabitation (non-cohabited single), legally married women and explored factors affecting birth outcomes of women in South Korea. A total of 790 842 singletons from married and 7788 singletons from unmarried women were examined based on the National Birth Registration Database of 2014-2015. Adjusted proportions for the occurrence of preterm births, low birth weight, and SGA were calculated and subgroup analyses were performed according to various factors like maternal age, parity, area of birth and maternal education. # Results Adjusted proportions of PTB (7.1%; 95% confidence interval (CI)=6.3-8.0, *P*-trend \<0.001), LBW (5.4%; 95% CI=4.7-6.1, *P*-trend \<0.001), and SGA (5.9%; 95% CI=5.2-6.7, *P*-trend=0.003) were significantly higher in non-cohabited single women compared to cohabited single and married women after adjusting for birth-related and socioeconomic factors. # Conclusions The findings provide a comprehensive evidence for increased risk of adverse birth outcomes that non-cohabited single women face compared to cohabited single and married women. The study also displays apparent need of reducing the health disparities single women experience during their pregnancies and need for enhanced welfare policies for unmarried mothers.